Her first lie : a thriller - Berry, Lucinda (The Perfect Child, 2026)
In this chilling prequel to The Perfect Child, USA Today bestselling author Lucinda Berry plunges readers into the dark origins of a family's secrets, where good intentions pave the road to unspeakable acts and a mother's love might be the deadliest inheritance of all. Becky Watson learned early that trust is a weapon and secrets are survival. From foster homes to abandoned backroads, she and her childhood confidant Orion have buried more than just memories. Now, as a college freshman, Becky's harboring her most dangerous secret yet: her newborn daughter, Janie. Desperation drives Becky to contact her estranged grandmother, Lillian. She swoops in like a guardian angel, but her salvation comes with a poisoned price tag. Behind Lillian's nurturing facade lurks a web of generational secrets. As buried truths claw their way to the surface, Becky faces an impossible choice: sacrifice her daughter or herself to break a twisted family legacy.